Responding to the crisis in United Nations peace operations. Issue 2 (3rd April 2021) - Kenkel, Kai Michael; Foley, Conor
ABSTRACT: This special forum discusses the future trajectory of UN peace operations at a time many stakeholders and analysts consider to be one of crisis, contestation, or at the very least transition. The UN is facing difficulties in responding effectively to many of the world's worst recent conflicts, even where it has (or until recently had) operations. Even before COVID-19, the blue helmets were facing a period of serious retrenchment and budgetary constraints. Mission mandates have experienced a transformation, from the recent "robust turn" to the incorporation of stabilization mandates grounded in counterinsurgency/counterterrorism doctrine. The crossroads of economic downturn, geopolitical realignment and continuous adaptation of peacekeeping practice provides the backdrop of the contributions to the special forum that follows. The analyses presented here not only accompany the ongoing evolution of the nexus of issues that constitute peacekeeping studies but also reflect the breadth and depth of the extensive attendant academic literature.